Influence of induced disease states on the disposition kinetic of imidocarb in dogs. - Abdullah, A. Salam; J. Desmod, Baggot (1985)
Disposition kinetics of imidocarb, an antiprotozoan drug, was studied in normal and febrile dogs. Fever was induced using E. coli endotoxin and Trypanosama evansi. The concentration of imidocarb in body fluids were measured by spectrophotometry. The disposition kinetics of imidocarb in normal and febrile dogs can be adequately described by a two-compartment open model. The result of the study indicate that fever of different etiologies affected the disposition kinetics of imidocarb differently. Plasma concentrations of imidocarb were higher than normal during endotoxin-induced fever and lower during trypanasoma-induced fever. The apparent volume of distribution, Vd (area), and the steady-state volume of distribution, Vd (ss), were significantly lowered in endotoxin induced febrile dogs than in normal dogs. However, the above kinetic parameters as well as volume of central compartment, V, and the body clearance, C1B, were significantly higher (P<0.01) in dogs during Trypanosoma induced fever than in normal animals, although the plasma concentrations were substantially reduced during the febrile reaction. The micro-constants were also affected differently by fever of different etiology. Nevertheless, half-life of imidocarb remained unaffected during the two febrile conditions. The present study also indicates that the influence of fever on pharmacokinetics should be considered beyond the plasma concentrations and half-like of the drug itself. The pathophysiology of the disease and not just the febrile state should be considered when evaluating the influence of disease conditions on the disposition kinetics of a drug.